R Inguinal/R Scrotum Extramammary Paget’s Disease with Diffuse Spine Metastasis Complicated by Microangiopathic Hemolytic Anemia - Alay Mansurov; Eric Christenson (Case Reports in Hematology)
A 47-year-old male presented with a groin lesion in 2011. Initial treatment with antifungals and vinegar was unsuccessful. In 2016, biopsy of this lesion was pursued with diagnosis of extramammary Paget’s disease (EMPD). Prior to the scheduled excision, he developed constant lower back pain with radiation to his lower extremities. MRI confirmed vertebral metastasis. Despite surgical and radiation therapy, his back pain progressed, and repeat imaging showed epidural spread of tumor in the thoracic spine. Later, the patient was admitted to the hospital due to severe anemia and thrombocytopenia. Further work-up confirmed the diagnosis of microangiopathic hemolytic anemia (MAHA). As we know, there are only few reports of spinal metastases in patients with EMPD. To the best of our knowledge, this is the first case report of EMPD complicated by MAHA.